Revisiting the conditioning variables of neuroplasticity induced by music training - Albusac-Jorge, Miriam (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Music training changes the brain both anatomically and functionally, where some variables conditioning the neuroplasticity. Here is a review of them, which include recent research in the neuroscience of music field. These variables are individual differences, sex, laterality, absolute pitch, instrument family, type of musical training received by the performer, training details –such as the intensity or age of onset, for example–, in addition to other environmental and genetic factors.